Molecular profiling of PYL gene family in sugar beet (Beta vulgaris L.) and BvPYL2/3 involved in ABA accumulation confers enhanced resistance to CLS (Cercospora Leaf Spot) - Wu, Changmei; Zhao, Chunlei; Li, Yanli; Ding, Guangzhou (Frontiers in Plant Science, 2025)
Cercospora leaf spot (CLS), caused by Cercospora beticola, is a major threat to sugar beet (Beta vulgaris L.) production globally. While abscisic acid (ABA) signaling mediates plant defense responses, the specific roles of ABA receptors (PYR/PYL/RCAR) in sugar beet resistance to CLS remain unclear. In this study, 10 BvPYL genes were identified from the sugar beet genome and functionally characterized. Transcriptome profiling showed that BvPYL2 displayed a stable constitutive expression profile in resistant and susceptible lines during infection, in contrast to BvPYL3, whose expression was marked by a significant decrease over the disease progression. Subcellular localization analysis revealed that both BvPYL2 and BvPYL3 localize to the plasma membrane, cytoplasm, and nucleus. Yeast two-hybrid assays demonstrated that BvPYL2 constitutively interacts with the negative regulator BvPP2C37, while BvPYL3 forms an ABA-dependent complex with BvPP2C37. Physiological observations showed that resistant plants achieved ABA-mediated stomatal closure to restrict pathogen entry, whereas susceptible plants maintained prolonged stomatal opening, facilitating infection. These results reveal two distinct regulatory mechanisms: BvPYL2 functions through constitutive interaction with BvPP2C37, and BvPYL3 operates via ABA-dependent signaling, both contributing to stomatal immunity against CLS. This study elucidates novel ABA-mediated defense mechanisms in sugar beet and identifies BvPYL2 and BvPYL3 as promising targets for breeding CLS-resistant germplasm.